Pengaruh Status Identitas terhadap Orientasi Masa Depan Area Pekerjaan - Novita Sari; Tarsono Tarsono; Elisa Kurniadewi (Psympathic : Jurnal Ilmiah Psikologi, 2016)
Based on the observation of the researcher, the lack of future orientation amongst students, particularly in the area of career, led by  deciding on study program was not deliberately when enroll in the university.  The research intended to obtain empirical data on the effect of the identity status on future orientation of the work area among students of the psychology program. The method used correlation study. The results showed that there was a significant influence of the identity status on the future orientation in working area. R square (R2) was 0.314, it meant 31.4% of the variation of the future orientation in working area influenced by the identity status. Three of the four identity statuses have a significant influence, namely the identity of achievement, the diffuse, and the moratorium. In despite there was correlation between foreclosure identity with future-orientation in working area  however there was not significant effect.